Growth, yield and quality of tomato fruits in narrow cultivation with the use of paclobutrazol (2017)
The aim of the study was to evaluate the effect of applying a paclobutrazol growth regulator on plants and plant spacing in the planting lines of industrial tomatoes was evaluated. The experiment was conducted from July to October. A randomized block strategy in a 5×2 factorial design (spacing x presence or absence of paclobutrazol) was used. The length of the main stem and stem diameter of the plants, chlorophyll content in leaves, total production (t ha-1), average number of fruits and fresh fruit weight, distribution of ripe, unripe and rotten fruits, number of ripe and unripe fruits, average weight of ripe and unripe fruits, soluble solids content, titratable acidity, pH, SS/TA ratio, percentage of compression and maximum strength to break and paclobutrazol residue in fruits were all determined. The results showed that Paclobutrazol influences the length of rods and chlorophyll content in leaves up to 15 days after transplanting, showing that the effect of the regulator is limited during the culture cycle. And, the regulator did not influence the production parameters of the industrial tomatoes. The application of PBZ did not influence any of the chemical or physical quality parameters that were evaluated. The plant densities studied did not alter the production and fruit quality components of the tomato. No residues of paclobutrazol were detected in tomato fruits for industrial processing that received an application of the regulator in the seedlings.